Flashpoints : the emerging crisis in Europe - Friedman, George (Doubleday, 2015)
"Friedman zooms in on the region that has, for five hundred years, been the cultural hotbed of the world--Europe--and examines the most basic and fascinating building block of the region: culture. Analyzing the fault lines that have existed for centuries--and which have led to two world wars and dozens more conflicts--Friedman walks us through the 'flashpoints' that are still smoldering beneath the surface and are on course to erupt again"--